The long-term restoration of ecosystem complexity - Moreno-Mateos, David; Alberdi, Antton; Morriën, Elly; van der Putten, Wim H.; Rodríguez-Uña, Asun; Montoya, Daniel (Nature ecology & evolution, 2020)
Multiple large-scale restoration strategies are emerging globally to counteract ecosystem degradation and biodiversity loss. However, restoration often remains insufficient to offset that loss. To address this challenge, we propose to focus restoration science on the long-term (centuries to millennia) re-assembly of degraded ecosystem complexity integrating interaction network and evolutionary potential approaches. This approach provides insights into eco-evolutionary feedbacks determining the structure, functioning and stability of recovering ecosystems. Eco-evolutionary feedbacks may help to understand changes in the adaptive potential after disturbance of metacommunity hub species with core structural and functional roles for their use in restoration. Those changes can be studied combining a restoration genomics approach based on whole-genome sequencing with replicated space-for-time substitutions linking changes in genetic variation to functions or traits relevant to the establishment of evolutionarily resilient communities. This approach may set the knowledge basis for future tools to accelerate the restoration of ecosystems able to adapt to ongoing global changes. Ecosystem restoration needs to incorporate network and evolutionary approaches to focus on long-term recovery of the complexity of ecosystems.